STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN ETOS KERJA GURU DI PAUDQ ASY-SYIFA KARAWANG - Amaliyah; Dewi Yanti; Mansur (UNISAN JURNAL, 2024)
Leadership is a person's ability to convince other people so that other people willingly work and are invited to carry out their wishes or ideas. The research aims to determine the work ethic of Islamic Religious Education (PAI) teachers at PAUDQ ASY-SYIFA Karawang and the leadership role of the principal in improving the work ethic of PAI teachers at PAUDQ ASY-SYIFA Karawang. The research method used is qualitative by interpreting a phenomenological perspective, namely how a researcher is able to understand and appreciate the leadership of the school principal in improving the work ethic of PAI teachers. This work ethic has experienced a decline as seen in several things which can be concluded, namely that there is no discipline towards PAI teachers. Based on their teaching, PAI teachers can master PAI material and various methods and have the motivation and freedom to develop their talents to support the learning process. PAI teachers are able to master the basics and principles of teaching according to the characteristics of students so that it is easier to choose the right learning method.